The Effect of Firm Size on Tax Aggressiveness with Moderating Role of Earnings Management - Nik Amah; Dwi Indah Setiowati; Almarida Wilujeng; Silvia Risky (Journal of Business and Management Review, 2022)
This study aims to find empirical evidence of the effect of firm size on tax aggressiveness and the moderating role of earnings management on this effect. The population in this study is the restaurant, hotel, tourism and transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2013-2019 period. The sampling technique used was purposive sampling, so that the sample data obtained was 80. Regression analysis and moderate regression analysis used to analyze the data. The results of this study indicate that firm size has no effect on tax aggressiveness. Earnings management moderate the effect of firm size on tax aggressiveness. Earnings management is a pure moderation on the effect of firm size on tax aggressiveness.